Fecal calprotectin levels in pediatric cow's milk protein allergy - Dominika Lendvai-Emmert; Dominika Lendvai-Emmert; Dominika Lendvai-Emmert; Vanessza Emmert; Vanessza Emmert; Alexandra Makai; Alexandra Makai; Katalin Fusz; Viktória Prémusz; Viktória Prémusz; Kata Eklics; Patrícia Sarlós; et al. (Frontiers Media S.A., 2022)
IntroductionThe most prevalent food allergy in younger children is cow's milk protein allergy (CMPA), a hypersensitivity reaction to cow's milk protein and its most common clinical manifestation is allergic colitis. The goal of our recent study was to assess somatic symptoms of CMPA and to prospectively observe the effects of a dairy elimination diet using objective parameters and questionnaires.MethodsThe County Hospital in Szekszárd, Hungary, investigated children aged 1 to 18 who had clinical signs that might indicate CMPA. Stool samples were taken and analyzed using a fecal calprotectin (FC) rapid test (Quantum Blue fCAL, Bühlmann Laboratories, Switzerland) at the time of the diagnosis and following 3 months of an elimination diet. At the baseline visit as well as the first and second follow-up, questionnaires were filled out. Patients were divided into two subgroups according to dietary guidelines based on the results of the questionnaires.ResultsA total of 47 patients participated in the study [42.55% female, mean age: 7.36 (SD 4.22) years]. There was no significant difference in FC levels between baseline and after 3-month elimination diet [73.98 (71.12) μg/g and 68.11 (74.4) μg/g, respectively, p = 0.331]. After three months, there was a significant decrease in FC levels among patients who adhered to the strict diet [84.06 (79.48) μg/g and 41.11 (34.24) μg/g, respectively, p = 0.001].ConclusionThe findings of our study suggest that FC can be an objective marker in confirming the diagnosis of CMPA. Significant improvement in clinical symptoms and in FC levels can only be expected after a strictly followed elimination diet.